2012
DOI: 10.1190/geo2011-0458.1
|View full text |Cite
|
Sign up to set email alerts
|

Crosshole GPR full-waveform inversion of waveguides acting as preferential flow paths within aquifer systems

Abstract: High-contrast layers caused by porosity or clay content changes can have a dominant effect on hydraulic processes within an aquifer. These layers can act as low-velocity waveguides for GPR waves. We used a field example from a hydrological test site in Switzerland to show that fullwaveform inversion of crosshole GPR signals could image a subwavelength thickness low-velocity waveguiding layer. We exploited the full information content of the data, whereas ray-based inversion techniques are not able to image suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
46
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 36 publications
3
46
0
Order By: Relevance
“…The starting relative permittivity and conductivity tomograms are usually obtained using a standard ray-based inversion that is employing the first-arrival times and first-cycle amplitudes. Applying the full-waveform inversion on several crosshole GPR data sets acquired in gravel aquifers in Switzerland and the U.S.A. shows that subwavelength thickness low-velocity wave guiding layers can be correctly imaged (Klotzsche et al, 2014(Klotzsche et al, , 2012, whereas ray-based inversion techniques are not able to image these thin waveguide layers because they only exploit the first-arrival times and first-cycle amplitudes. Converting the permittivity results into porosity and comparing them with NeutronNeutron logging data showed a good correspondence (Klotzsche et al, 2014.…”
Section: Full-waveform Inversion Of Crosshole Gpr Datamentioning
confidence: 96%
“…The starting relative permittivity and conductivity tomograms are usually obtained using a standard ray-based inversion that is employing the first-arrival times and first-cycle amplitudes. Applying the full-waveform inversion on several crosshole GPR data sets acquired in gravel aquifers in Switzerland and the U.S.A. shows that subwavelength thickness low-velocity wave guiding layers can be correctly imaged (Klotzsche et al, 2014(Klotzsche et al, , 2012, whereas ray-based inversion techniques are not able to image these thin waveguide layers because they only exploit the first-arrival times and first-cycle amplitudes. Converting the permittivity results into porosity and comparing them with NeutronNeutron logging data showed a good correspondence (Klotzsche et al, 2014.…”
Section: Full-waveform Inversion Of Crosshole Gpr Datamentioning
confidence: 96%
“…Seismic FWI cannot be used to invert GPR data since the pertaining vectorial wave propagation and radiation patterns are different. Recent developments in FWI of crosshole (Ernst et al, 2007a,b;Kuroda et al, 2007;Klotzsche et al, 2010Klotzsche et al, , 2012Klotzsche et al, , 2013Meles et al, 2010Meles et al, , 2011, off-ground (Kalogeropoulos et al, 2011(Kalogeropoulos et al, , 2013Lambot et al, 2004), and surface GPR (Busch et al, 2012) use significant information in the measured data and indicate the benefits of FWI inversion approach to estimate quantitative permittivity and conductivity values. A vectorial approach was implemented that honors the vectorial EM wave propagation and simultaneously updates the permittivity and conductivity .…”
Section: Full-waveform Inversionmentioning
confidence: 98%
“…In subsequent iterations, these steps are repeated using the updated model until the residual wavefield is less than a certain percentage (0.5% or 1%) of its value compared to the previous iteration. For inverting experimental data, a starting model and effective source wavelet needs to be estimated (Klotzsche et al, 2010(Klotzsche et al, , 2012 from which a first cut solution is calculated that should match the observed waveforms received in the field experiment within half the dominant pulse period. Otherwise, the inversion will proceed to update in the wrong direction and results in a phenomenon called local minimum trapping (Isernia et al, 2001;Meles et al, 2011).…”
Section: Full-waveform Inversionmentioning
confidence: 99%
“…FWI of cross-hole GPR datasets has shown its efficiency on synthetic and real [1] cases. Here, we perform FWI in carbonate environment with the favorable cross-hole configuration in order to evaluate our multi-parameter inversion algorithm.…”
Section: Introductionmentioning
confidence: 99%